Brand-name drug, generic drug, orphan drug. Pharmacological therapy with biosimilar drugs – provision of due diligence in the treatment process - Zajdel, Justyna; Zajdel, Radosław (Contemporary Oncology/Współczesna Onkologia, 2013)
Due diligence in the process of provision of healthcare services refers, among other elements, to the application of pharmacological therapy at a time which offers the greatest chance for a successful outcome of treatment, i.e. for achieving the optimum expected effect understood as an improvement in the patient’s health, reduction of health risks or elimination of the disease. However, due diligence may also refer to actions aimed at ensuring that neither the patient nor the healthcare payer is required to incur unreasonable costs in the process of treatment. The validity of that statement stems not only from normative acts but also from ethical standards laid down in the Medical Code of Ethics (Article 57 section 2). It often happens that the provision of optimal treatment calls for deviations from the formal provisions included in Summary Product Characteristics (SPCs), and the application of drugs that are bioequivalent to reference drugs, which translates into a significant reduction of costs. The present study addresses the problem of acceptability of a specific form of drug substitution consisting in the replacement of a reference drug with a generic drug. Also explored are legal aspects associated with the possibility of therapy based on “off-label use”. The study reviews normative acts existing in the Polish and EU legislation. It also provides a clear definition of orphan drug, which has made it possible to make a distinction and investigate mutual relations between the concepts of brand-name (reference) drug, orphan drug and generic drug.